Pengaruh Aktivitas Fisik dan Mental Terhadap Prestasi Akademik Siswa: Sebuah Kajian Literatur di Lingkungan Sekolah - Aslan Aslan (Jurnal Kesehatan, 2024)
This study aims to explore the influence of physical and mental activity on students' academic achievement through a literature review in a school setting. Physical and mental activity are important components in children's health and cognitive development, which have the potential to influence their learning outcomes. This research reviewed various literature and empirical studies that focused on the relationship between these two types of activities and students' academic scores. It was found that regular physical activity can improve concentration, strengthen memory and reduce stress, all of which have a positive impact on academic performance. Meanwhile, mental activities such as brain games and mindfulness techniques improve students' critical thinking and creativity. The conclusions of this study underscore the importance of integrating physical and mental activity programmes in the school curriculum to maximise students' academic potential. The study recommends increased collaboration between educators, policy makers and health experts to create a balanced learning environment that supports students' holistic development.